Spanish as the language of translation in Spain and Latin America: Shakespeare’s retranslations as a case in point. - Zaro-Vera, Juan Jesús (My University, 2019)
A short description of the linguistic decisions taken by three Argentinian translators of Shakespeare (Rafael Squirru, Miguel Ángel Montezanti and Carlos Gamerro) with respect to the language of translation (Spanish). In the three cases, they try to reflect the regional variety known as "ríoplatense", although in different degrees and for different reasons.
Keywords: Shakespeare; Traducción; Retranslation; Language of translation; Shakespeare